Hubungan minat belajar terhadap hasil belajar matematika siswa kelas V SD - Lestari, Eci Anita; Maulida, Ikrima; Agung, Anugrah (Yayasan Mitra Persada Nusantara, 2024)
The aim of this research is to analyse the relationship between interest and mathematics learning outcomes of class V students at SD Negeri 66 Bengkulu City. The type of research used is quantitative with correlation methods. The sample in this research was 50 students from class V of SD Negeri 66 Bengkulu City. Data collection techniques in this research used questionnaire techniques and documentation techniques. The data analysis technique uses the r test and the Pearson correlation test with the help of the Statistical Product for Servicer Solution (SPSS) 22 program. Based on the research results from the questionnaire for variable amounted to 0.279 and obtained a calculated r value of 0.843. So r calculated 0.843 > r table 0.279 so it can be concluded that H0 is rejected and Ha is accepted. From the results of the Pearson correlation calculation, it is 0.843, which means that the degree of relationship between interest and mathematics learning outcomes has a very strong relationship and the direction of the relationship is positive, which means that the greater the student's interest, the greater the value they will obtain and vice versa.